Efektivitas Sistem Informasi Kearsipan Dinamis dalam Pengelolaan Arsip Dinamis di Dinas Perpustakaan dan Kearsipan Kota Pekanbaru - Nera Mailanda; Nining Sudiar; Triono Dul Hakim (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2020)
The purpose of this study was to determine how effective the use of SIKD in managing archives in the Pekanbaru City Library and Archives Service. The research method used is quantitative descriptive method, with data collection done through observation, questionnaires, interviews, documentation and literature study. The questionnaire was distributed to the archive manager with a research sample of 6 people. The results of this study indicate that the average score is 3.35, based on preparations using the Likert scale at intervals of 3.26 - 4.00, that the archive manager is very positive and effective using SIKD in managing the archives at the Department of Library and Archives of Pekanbaru City . And the obstacle faced by managers in using SIKD is one of the network problems, where in the Pekanbaru City Library and Archives Service the network is sometimes unstable.